PELATIHAN PENGOLAHAN LIDI SAWIT MENJADI PIRING PESTA UNTUK MENINGKATKAN PEREKONOMIAN MASYARAKAT DI DESA ADIPURA KENCANA KEC. BAHAR SELATAN KABUPATEN MUARO JAMBI - Mailindra, Wiyan; Azhar, Azhar; Desiana, Desiana; Helfenta, Helfenta (Institut Agama Islam Negeri Kerinci, 2022)
Indonesian handicraft products always give a nuance to a variety of beauty. Various materials used also affect the result of a craft product. Starting from recycled materials, materials made from nature, or materials that are relatively inexpensive to expensive, materials can be utilized as the basic ingredients of handicrafts. Crafts are creative activities related to creating, producing, and distributing products made by craftsmen, starting from the initial design until the product completion process. The craft includes goods made from natural fibers, leather, rattan, wood, glass, fabric, marble, clay, lime, and metal. Processing palm fiber into a plate Party in the village Adipura Kencana Kec. Bahar Selatan Kab. Muaro Jambi can add insight and experience to their work by exploiting palm oil sticks as raw material for making handicraft products using the ATBM weaving technique, and it is expected to spur more maximal work again for the creation of perfection of a work of crafts.